Giving Children a Voice: Children’s Perceptions of Pain and Pain Management within the Paediatric Emergency Department - Pope, Nicole (Curtin University, 2018)
Using the draw write and tell technique children’s experiences of pain in a hospital emergency department were explored. Transcripts from 15 children were analysed and two main themes identified; ‘My Pain’ and ‘Comfort and relief’. Findings highlighted the importance of fostering a sense of security for children in pain and identified their capacity to contribute to managing their pain. Nurses need to pay attention to the psychosocial dimensions of pain and incorporate non-pharmacological strategies.